(untitled) (London Journal of Medical and Health Research, 2026)
The legislative framework for undesirable substances in EU territory is explained at first with parallel commenting on the political dimension involved in this issue as regards the sector of animal feeding. Then, a brief account on developments of Community legislation in this field is given, with paying particular emphasis on the delicate subject of “dilution principle”. In turn, reference is made to methods available for the analysis of undesirable substances in feeds. Furthermore, the article focuses on two groups of undesirable substances, i.e. firstly mycotoxins, where reference is made to legislative developments in this issue as well as prevention measures, and secondly, dioxins where a look is thrown to the historical background in this subject, while focusing on the dioxin episode in Belgium but also on subsequent findings. The legislative tools to confront problems of undesirable substances presence in the sector of animal nutrition is discussed, concluding with the importance of environmental dimension. Finally, reference is made to developments in Community Legislation for dioxins and mycotoxins during the last decade.